Space Needle (C.P. Johnston Co.)
Topping the 1962 Seattle World's Fair is the 600-foot Space Needle, where visitors to Seattle from April 21 through October 21, 1962 can dine in a 250-seat revolving restaurant affording a panoramic view of the world's fair, city, and mountains around this seaport. Tying the fair to downtown Seattle is the world's high speed mass transit Monorail, shown here at the base of the Needle.